Exploration of a wide bandgap semiconducting supramolecular Mg(II)-metallohydrogel derived from an aliphatic amine: a robust resistive switching framework for brain-inspired computing - Kripasindhu Karmakar; Arpita Roy; Subhendu Dhibar; Shantanu Majumder; Subham Bhattacharjee; S. K. Mehebub Rahaman; Ratnakar Saha; Priyajit Chatterjee; Soumya Jyoti Ray; Bidyut Saha (Scientific Reports, 2023)
Abstract A rapid metallohydrogelation strategy has been developed of magnesium(II)-ion using trimethylamine as a low molecular weight gelator in water medium at room temperature. The mechanical property of the synthesized metallohydrogel material is established through the rheological analysis. The nano-rose like morphological patterns of Mg(II)-metallohydrogel are characterized through field emission scanning electron microscopic study. The energy dispersive X-ray elemental mapping analysis confirms the primary gel forming elements of Mg(II)-metallohydrogel. The possible metallohydrogel formation strategy has been analyzed through FT-IR spectroscopic study. In this work, magnesium(II) metallohydrogel (Mg@TMA) based metal–semiconductor-metal structures have been developed and charge transport behaviour is studied. Here, it is confirmed that the magnesium(II) metallohydrogel (Mg@TMA) based resistive random access memory (RRAM) device is showing bipolar resistive switching behaviour at room temperature. We have also explored the mechanism of resistive switching behaviour using the formation (rupture) of conductive filaments between the metal electrodes. This RRAM devices exhibit excellent switching endurance over 10,000 switching cycles with a large ON/OFF ratio (~ 100). The easy fabrication techniques, robust resistive switching behaviour and stability of the present system makes these structures preferred candidate for applications in non-volatile memory design, neuromorphic computing, flexible electronics and optoelectronics etc.